The Impact of Schooling and Industrial Restructuring on Recent Trends in Wage Inequality in the United States - Bluestone, Barry (American Economic Review, 1990)
Sufficient evidence now exists to confirm a strong rising trend in wage inequality in the United States since at least the mid-1970s. Still elusive is a definitive explanation for this tendency. In the pursuit of one, researchers have now begun to turn their attention to two factors: 1) on the supply side, an apparent rapid growth in the rates of return to education; and 2) on the demand side, an acceleration in industrial restructuring, in particular, the shift in employment from goods production to services. In this connection, the decline in unionization and the expanded exposure of the manufacturing sector to international competition have received renewed consideration. This paper contends that it is precisely the increasing returns to schooling in both goods and services in combination with the shift in employment between the two that is responsible for the recent growth in wage dispersion.